Echocardiography in a critical care unit: a contemporary review. (2nd January 2022) - Mohsin, Muhammad; Farooq, Muhammad Umar; Akhtar, Waheed; Mustafa, Waqar; Rehman, Tanzeel Ur; Malik, Jahanzeb; Zahid, Taimoor
ABSTRACT: Introduction: Echocardiography is a rapid, noninvasive, and complete cardiac assessment tool for patients with hemodynamic instability. Relevant articles were extracted after searching on databases by two reviewers and incorporated in this review in anarrative style. Areas covered: his review provides an overview of the evidence for current practices in critical care units (CCUs), incorporating the use of echocardiography in different etiologies of shock. Expert opinion: In an acute scenario, a basic echocardiographic study yields prompt diagnosis, allowing for the initiation of treatment. The most common pathologies in shocked patients are identified promptly using two-dimensional (2D) and M-mode echocardiography. A more comprehensive assessment can follow after patients have been stabilized. There are four types of shock: (i) cardiogenic shock, (ii) hypovolemic shock, (iii) obstructive shock, and (iv) septic shock. All of them can be readily identified by echocardiography. As echocardiography is increasingly being used in an intensive care setting, its applications and evidence base should be expanded by randomized controlled trials to demonstrate patient outcomes in critical care.